Potassium ion battery negative electrode material and preparation method and application thereof

CN117976834BActive Publication Date: 2026-10-23LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211310434.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2026-10-23
Estimated Expiration
2042-10-25

AI Technical Summary

Benefits of technology

[0030]所述载气为氩气或氮气,流速为0.5L/min-8L/min,通入时间为20min-4小时。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117976834B_ABST
    Figure CN117976834B_ABST
Patent Text Reader

Abstract

The application discloses a kind of potassium ion battery negative electrode material and its preparation method and application, potassium ion battery negative electrode material includes: stannous oxide and the composite matrix of nano titanium carbide, and titanium carbide coating layer is coated in the outer surface of composite matrix;Composite matrix is obtained by making nano titanium carbide evenly dispersed distribution in the matrix of stannous oxide by chemical vapor deposition method;The mass of nano titanium carbide accounts for the percentage of total mass of composite matrix 2% 20%;The mass of titanium carbide coating layer accounts for the percentage of total mass of potassium ion battery negative electrode material 0.5% 10%;The potassium ion battery negative electrode material provided by the application is applied to potassium ion battery, by the titanium carbide of inside and outside coating of matrix jointly, make potassium ion battery have lower volume expansion, better electric conductivity and long cycle life characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of potassium-ion battery materials technology, and in particular to a potassium-ion battery anode material, its preparation method, and its application. Background Technology

[0002] With the ever-increasing demand for green energy in modern society, the scarcity of lithium resources and rising costs have posed challenges to the further development of lithium-ion batteries. Potassium-ion batteries (KIBs), as an alternative to traditional lithium-ion batteries (LIBs), share many similarities with mature LIB technologies, such as storage mechanisms and electrolyte configurations. Their low cost, high voltage, and similar operating principles have attracted widespread research interest. Although significant progress has been made in KIB research in recent years, there are still significant differences between KIBs and other alkaline ion batteries. This results in poor electrochemical performance when KIBs directly utilize other alkaline ion battery systems, making them unable to compete with mature LIB technologies.

[0003] Tin and its oxides are considered by many researchers to be highly promising potassium-based battery anode materials due to their high theoretical capacity. Furthermore, their abundant and inexpensive availability has made them an important anode material for batteries. However, single-structure tin-based materials are subject to changes in K... + The insertion and extraction of materials can cause severe volume expansion and contraction, making the material prone to pulverization and collapse, resulting in severe capacity decay of the battery.

[0004] In addition, K + The radius of (1.38) is greater than that of Li. + (0.76) and Na + The radius of (1.02) is much larger, which leads to slower reaction kinetics and relatively low electrical conductivity of tin-based materials.

[0005] Therefore, the current research goal for tin-based anode materials is to overcome the drastic volume changes of tin-based materials during charge-discharge cycles, improve their structural stability, and ultimately enhance their cycle stability and high current rate performance. Summary of the Invention

[0006] This invention provides a potassium-ion battery anode material, its preparation method, and its application. The aim is to solve the problems of large volume expansion, poor conductivity, and poor cycle life in tin suboxide anode materials during potassium ion intercalation / deintercalation. This invention uses chemical vapor deposition to uniformly disperse titanium carbide in a tin suboxide matrix, and then coats the surface of the composite matrix of tin suboxide and nano-titanium carbide with a titanium carbide layer. On the one hand, utilizing the high hardness of titanium carbide, the internal titanium carbide, as an inert component that does not undergo potassium ion intercalation / deintercalation, can prevent the agglomeration of the tin suboxide active material, and on the other hand, it interacts with the surface... The titanium carbide coating stabilizes the material's structure, buffering the volume expansion during the potassium ion insertion / extraction process in tin oxide during cycling. Furthermore, the high conductivity of titanium carbide allows both doped and coated titanium carbide to accelerate potassium ion conduction within tin oxide and enhance the overall conductivity of the negative electrode particles. Applying the potassium-ion battery negative electrode material provided by this invention to potassium-ion batteries, through the combined effect of the internal and external titanium carbide coatings, results in lower volume expansion, better conductivity, and longer cycle life.

[0007] In a first aspect, embodiments of the present invention provide a potassium-ion battery anode material, the potassium-ion battery anode material comprising: a composite matrix of stannous oxide and nano-titanium carbide, and a titanium carbide coating layer covering the outer surface of the composite matrix;

[0008] The composite matrix is ​​obtained by uniformly dispersing the nano-titanium carbide in the tin oxide matrix through chemical vapor deposition.

[0009] The mass percentage of the nano-titanium carbide in the total mass of the composite matrix is ​​2%-20%;

[0010] The mass of the titanium carbide coating layer accounts for 0.5%-10% of the total mass of the potassium-ion battery anode material.

[0011] Preferably, the average particle size Dv50 of the potassium-ion battery anode material is between 1 nm and 100 μm;

[0012] The mass percentage of the nano-titanium carbide in the total mass of the composite matrix is ​​4%-15%.

[0013] The mass of the titanium carbide coating layer accounts for 1.5%-6% of the total mass of the potassium-ion battery anode material.

[0014] Secondly, embodiments of the present invention provide a method for preparing the potassium-ion battery anode material described in the first aspect above, the method comprising:

[0015] A mixture of tin powder, tin dioxide, titanium source material, and hydrocarbons is placed in a high-temperature vacuum furnace and subjected to high-temperature heat treatment under a first reduced pressure condition to vaporize the mixture and obtain a first mixed gas; or a mixture of tin powder and tin dioxide is placed in a vacuum high-temperature furnace and subjected to high-temperature heat treatment under a second reduced pressure condition until the mixture vaporizes, and then the gas of titanium source material and hydrocarbons is introduced and thoroughly mixed to obtain a second mixed gas.

[0016] The first or second mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled, and deposited on a stainless steel substrate to obtain the precursor material.

[0017] After the precursor material is crushed and sieved, it is then coated with titanium carbide to obtain the potassium-ion battery anode material.

[0018] Preferably, the titanium source material includes one or more of the following: titanium tetrachloride, metallic titanium powder, titanium hydride, titanium hydroxide, titanium dioxide, titanium tetrachloride, titanium tetrabutyl ester, and ethyl acetoacetate titanium.

[0019] The hydrocarbons include one or more of the following: methane, acetylene, ethylene, propylene, natural gas, propane, toluene, acetone, phenolic resin, and asphalt.

[0020] Preferably, the high-temperature heat treatment under the first reduced pressure condition specifically involves: evacuating to 1 Pa-200 Pa, heating to 1000℃-2000℃ and holding at that temperature for 0.5 hours-5 hours;

[0021] The high-temperature heat treatment under the second decompression condition specifically involves: evacuating to 1Pa-200Pa, heating to 1000℃-2000℃ and holding at that temperature for 0.5 hours-5 hours.

[0022] Preferably, the method for introducing the titanium source material gas and the hydrocarbon gas includes: directly introducing the titanium source material gas and the hydrocarbon gas into the high-temperature vacuum furnace, or introducing the titanium source material gas and the hydrocarbon gas into the high-temperature vacuum furnace by means of a carrier gas in a bubbling manner;

[0023] The flow rate of the gas containing the titanium source material directly introduced into the high-temperature vacuum furnace is 2L / min-15L / min, and the introduction time is 20min-4 hours.

[0024] The flow rate of the hydrocarbon gas directly introduced into the high-temperature vacuum furnace is 2L / min-15L / min, and the introduction time is 20min-4 hours.

[0025] The carrier gas is argon or nitrogen, with a flow rate of 0.5 L / min to 8 L / min and an introduction time of 20 min to 4 hours.

[0026] Preferably, the method for coating titanium carbide specifically involves: placing a mixed powder of titanium source material and hydrocarbon in a high-temperature vacuum furnace, heat-treating it at high temperature under a third reduced pressure until the mixed powder vaporizes to obtain a third mixed gas, and then using a carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace containing the precursor material, so that the third mixed gas is cooled and deposited onto the surface of the precursor material, and after discharge, it is crushed, sieved and demagnetized to obtain potassium-ion battery anode material;

[0027] The titanium source material includes one or more of the following: titanium tetrachloride, metallic titanium powder, titanium hydride, titanium hydroxide, titanium dioxide, titanium tetrachloride, titanium tetrabutyl ester, and ethyl acetoacetate titanium.

[0028] The hydrocarbons include one or more of the following: methane, acetylene, ethylene, propylene, natural gas, propane, toluene, acetone, phenolic resin, and asphalt;

[0029] The high-temperature heat treatment under the third reduced pressure condition specifically involves: evacuating to 1Pa-200Pa, heating to 1000℃-2000℃ and holding at that temperature for 0.5 hours-5 hours;

[0030] The carrier gas is argon or nitrogen, with a flow rate of 0.5 L / min to 8 L / min and an introduction time of 20 min to 4 hours.

[0031] Thirdly, embodiments of the present invention provide a negative electrode sheet, the negative electrode sheet comprising the potassium-ion battery negative electrode material described in the first aspect above.

[0032] Fourthly, embodiments of the present invention provide a potassium-ion battery, the potassium-ion battery comprising the negative electrode sheet described in the third aspect above.

[0033] This invention provides a potassium-ion battery anode material. Titanium carbide is uniformly dispersed in a tin oxide matrix using chemical vapor deposition (CVD), and a titanium carbide layer is coated onto the surface of the composite matrix of tin oxide and nano-titanium carbide. On one hand, utilizing the high hardness of titanium carbide, the internal titanium carbide, as an inert component that does not undergo potassium ion insertion / extraction, can prevent the agglomeration of the tin oxide active material. Together with the outer surface titanium carbide, it stabilizes the material's structure, buffering the volume expansion during potassium ion insertion / extraction from tin oxide during cycling. On the other hand, utilizing the high conductivity of titanium carbide, the doped and coated titanium carbide not only accelerates the conduction rate of potassium ions within the tin oxide matrix but also enhances the overall conductivity of the anode particles.

[0034] The potassium-ion battery anode material provided by this invention is applied in potassium-ion batteries. Through the combined action of titanium carbide inside and outside the matrix, the potassium-ion battery has the characteristics of low volume expansion, good conductivity and long cycle life. Attached Figure Description

[0035] The technical solutions of the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples.

[0036] Figure 1 This is a flowchart of the preparation of potassium-ion battery anode materials provided in the embodiments of the present invention;

[0037] Figure 2 These are cycle curves of a battery assembled with the potassium-ion battery anode material provided in Example 1 of the present invention and a battery assembled with the tin oxide battery anode material of Comparative Example 1. Detailed Implementation

[0038] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, it should be understood that these embodiments are only for more detailed description and should not be construed as limiting the present invention in any way, that is, not intended to limit the scope of protection of the present invention.

[0039] This invention provides a potassium-ion battery anode material, comprising: a composite matrix of tin oxide and nano-titanium carbide, and a titanium carbide coating layer on the outer surface of the composite matrix; the average particle size Dv50 of the potassium-ion battery anode material is between 1 nm and 100 μm, preferably between 500 nm and 10 μm.

[0040] The composite matrix of tin oxide and nano-titanium carbide is obtained by uniformly dispersing nano-titanium carbide in the tin oxide matrix through chemical vapor deposition; the mass percentage of nano-titanium carbide in the total mass of the composite matrix is ​​2%-20%, preferably 4%-15%.

[0041] The mass percentage of the titanium carbide coating layer in the total mass of the potassium-ion battery anode material is 0.5%-10%, preferably 1.5%-6%.

[0042] This invention provides a method for preparing the above-mentioned potassium-ion battery anode material, such as... Figure 1 As shown, the specific steps include:

[0043] Step 110: Place the mixture of tin powder, tin dioxide, titanium source material and hydrocarbon in a high-temperature vacuum furnace and perform high-temperature heat treatment under a first reduced pressure condition to vaporize the mixture and obtain a first mixed gas; or place the mixture of tin powder and tin dioxide in a vacuum high-temperature furnace and perform high-temperature heat treatment under a second reduced pressure condition until the mixture is vaporized, then introduce the gas of titanium source material and hydrocarbon, and after thorough mixing, obtain a second mixed gas;

[0044] Among them, the titanium source materials include one or more of the following: titanium tetrachloride, metallic titanium powder, titanium hydride, titanium hydroxide, titanium dioxide, titanium tetrachloride, titanium tetrabutyl ester, and ethyl acetoacetate titanium.

[0045] Hydrocarbons include one or more of the following: methane, acetylene, ethylene, propylene, natural gas, propane, toluene, acetone, phenolic resin, and asphalt;

[0046] High-temperature heat treatment is carried out under the first decompression condition, specifically: vacuuming to 1Pa-200Pa, heating to 1000℃-2000℃ and holding for 0.5 hours-5 hours;

[0047] High-temperature heat treatment is carried out under the second decompression condition, specifically: vacuuming to 1Pa-200Pa, heating to 1000℃-2000℃ and holding for 0.5 hours-5 hours;

[0048] There are two methods for introducing gases from the titanium source material and hydrocarbon gases:

[0049] The first method is to directly introduce a gas containing titanium source material and a gas containing hydrocarbons into a high-temperature vacuum furnace; the flow rate of the gas containing titanium source material is 2L / min-15L / min, and the introduction time is 20min-4 hours; the flow rate of the gas containing hydrocarbons is 2L / min-15L / min, and the introduction time is 20min-4 hours.

[0050] The second method is to introduce the gaseous titanium source material and hydrocarbon gas into a high-temperature vacuum furnace by bubbling using a carrier gas; the carrier gas is argon or nitrogen, the flow rate is 0.5L / min-8L / min, and the introduction time is 20min-4 hours.

[0051] Step 120: The first mixed gas or the second mixed gas is introduced into the collection chamber of the high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0052] Step 130: After crushing and sieving the precursor material, it is then coated with titanium carbide to obtain the potassium-ion battery anode material.

[0053] Specifically, the method for titanium carbide coating is as follows: a mixture of titanium source material and hydrocarbon powder is placed in a high-temperature vacuum furnace and heat-treated at high temperature under a third reduced pressure until the mixed powder is vaporized to obtain a third mixed gas. The third mixed gas is carried into the collection chamber of the high-temperature vacuum furnace containing the precursor material by a carrier gas, so that the third mixed gas is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved and demagnetized to obtain potassium-ion battery anode material.

[0054] Among them, the titanium source materials include one or more of the following: titanium tetrachloride, metallic titanium powder, titanium hydride, titanium hydroxide, titanium dioxide, titanium tetrachloride, titanium tetrabutyl ester, and ethyl acetoacetate titanium.

[0055] Hydrocarbons include one or more of the following: methane, acetylene, ethylene, propylene, natural gas, propane, toluene, acetone, phenolic resin, and asphalt;

[0056] High-temperature heat treatment under the third decompression condition is specifically as follows: vacuuming to 1Pa-200Pa, heating to 1000℃-2000℃ and holding for 0.5 hours-5 hours;

[0057] The carrier gas introduced into the collection chamber of the high-temperature vacuum furnace is argon or nitrogen, with a flow rate of 0.5 L / min to 8 L / min and a transit time of 20 min to 4 hours.

[0058] The potassium-ion battery anode material described above in this embodiment of the invention can be used as an anode active material in anode sheets. These anode sheets can be applied to potassium-ion batteries. Through the combined action of titanium carbide coating inside and outside the potassium-ion battery anode material matrix, the potassium-ion battery exhibits characteristics such as low volume expansion, good conductivity, and long cycle life.

[0059] To better understand the technical solution provided by this invention, the following examples illustrate the preparation method and characteristics of the potassium-ion battery anode material of this invention.

[0060] Example 1

[0061] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0062] 1) Weigh 1 kg of tin powder, 1 kg of tin dioxide powder, 130 g of titanium hydride and 100 g of asphalt, mix them evenly and place them in a high-temperature vacuum furnace, evacuate to 20 Pa, heat to 1800 ℃, and keep warm for 2 hours to obtain the first mixed gas.

[0063] 2) The first mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0064] 3) After crushing and sieving the precursor material, titanium carbide coating treatment is performed. Specifically, 100g of titanium hydride and 80g of asphalt are mixed evenly and placed in a high-temperature vacuum furnace. The vacuum is evacuated to 50Pa, heated to 1800℃, and held for 2 hours to obtain a third mixed gas. Argon gas with a flow rate of 2L / min is introduced as the carrier gas to carry the above third mixed gas into the collection chamber of the high-temperature vacuum furnace. The gas is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved, and demagnetized to obtain potassium-ion battery anode material.

[0065] The potassium-ion battery anode material with a titanium carbide coating prepared in this embodiment was used to prepare a negative electrode sheet, and coin cell half-cells and full cells were assembled for testing:

[0066] Preparation method of button half cell: A novel potassium-ion battery negative electrode material with carbon coating, conductive additive carbon black and binder polyvinylidene fluoride (PVDF) are weighed at a mass ratio of 7:2:1. At room temperature, the mixed materials and solvent N-methylpyrrolidone (NMP) are put into a pulping machine to prepare a slurry. Then, the slurry is coated on copper foil, dried and cut into pieces. In a glove box, a button half cell is assembled with potassium metal as the counter electrode, glass fiber membrane as the separator, and 0.8M potassium hexafluorophosphate (dissolved in ethylene carbonate / diethyl carbonate (EC / DMC) at a volume ratio of 1:1) as the electrolyte.

[0067] Test method for button half-cells: The prepared button half-cells were tested in constant current charge and discharge mode using a charge and discharge instrument. The discharge cutoff voltage was 0.01V and the charging cutoff voltage was 3V. The first charge and discharge capacity and initial efficiency performance were tested. The test data are shown in Table 1.

[0068] Preparation and testing of full cells:

[0069] Preparation of the negative electrode sheet: A novel potassium-ion battery negative electrode material with a carbon coating layer was prepared by combining graphite with a specific capacity of 450 mAh / g. This composite was then weighed and mixed with conductive additive carbon black and binder PVDF in a ratio of 7:2:1. At room temperature, the mixed material and solvent NMP were placed in a slurry mixer to prepare a slurry. The prepared slurry was uniformly coated onto copper foil at a coating speed between 2.2 m / min and 3.5 m / min, with the coating machine's drying tunnel temperature between 70℃ and 100℃. After double-sided drying in the coating machine, the negative electrode sheet was obtained.

[0070] Preparation of the positive electrode: Weigh out the positive electrode material potassium ferrous cyanide (KFe) in a mass ratio of 8:1:1. 2+ [Fe 3+[CN]6] Conductive additive carbon black and binder PVDF are mixed; at room temperature, the mixed materials and solvent NMP are put into a pulping machine to prepare a slurry; the prepared slurry is uniformly coated on aluminum foil at a coating speed of 2.0 m / min-3.0 m / min and the baking track temperature of the coating machine is 90℃-120℃; after double-sided coating and drying by the coating machine, a positive electrode sheet is obtained.

[0071] Battery fabrication: The positive electrode of the positive electrode sheet is exposed using aluminum tabs, and the negative electrode sheet is exposed using copper-plated nickel tabs. The prepared positive and negative electrodes and separator are wound into a bare cell. The cell is then encapsulated with aluminum-plastic film using a heat-sealing process. High-temperature vacuum baking is used to remove moisture from the battery. Then, 1 mole of electrolyte is injected. The electrolyte is a mixed solution of KPF6 and ethylene carbonate / dimethyl carbonate (EC / DMC, volume ratio 1:1). After vacuum sealing, the battery is obtained.

[0072] Testing: Constant current charge and discharge mode tests were conducted using a charge and discharge instrument. The discharge cutoff voltage was 2.0V and the charging cutoff voltage was 4.5V. Discharge tests after the first week were all conducted at a 1C current density.

[0073] The cycle curve of the full battery prepared in this embodiment is shown in the figure below. Figure 2 As shown, the test results of the cycle retention rate at 1C magnification for 100 and 300 cycles are detailed in Table 1.

[0074] Example 2

[0075] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0076] 1) Weigh 1 kg of tin powder and 1 kg of tin dioxide powder, mix them evenly, and place them in a high-temperature vacuum furnace. Evacuate the furnace to 60 Pa, heat it to 1400℃, and hold it for 1 hour to obtain a tin-containing mixed gas. Introduce acetylene gas at a flow rate of 3 L / min into the high-temperature vacuum furnace, and introduce the titanium tetrachloride-containing gas into the high-temperature vacuum furnace by bubbling through argon gas at a flow rate of 5 L / min. The two gases are introduced for 130 min and mixed evenly with the tin-containing mixed gas. The temperature in the high-temperature furnace is 1400℃, and it is held for 2 hours to obtain a second mixed gas.

[0077] 2) The second mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0078] 3) After the precursor material is crushed and sieved, it is then coated with titanium carbide. Specifically, the high-temperature vacuum furnace is evacuated to 50 Pa and heated to 1800 °C. Acetylene gas at a flow rate of 2 L / min and argon gas containing titanium tetrachloride at a flow rate of 2 L / min are introduced by bubbling for 90 min and kept at this temperature for 2 hours to obtain a third mixed gas. Argon gas at a flow rate of 6 L / min is introduced as the carrier gas to carry the above third mixed gas into the collection chamber of the high-temperature vacuum furnace. The gas is cooled and deposited on the surface of the above precursor material. After discharge, the material is crushed, sieved and demagnetized to obtain potassium-ion battery anode material.

[0079] The potassium-ion battery anode material prepared in this embodiment was used to prepare a negative electrode sheet, and the battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0080] Example 3

[0081] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0082] 1) Weigh 1.5 kg of tin powder, 1 kg of tin dioxide powder, 130 g of metallic titanium powder and 410 g of phenolic resin, mix them evenly and place them in a high-temperature vacuum furnace. Evacuate to 70 Pa, heat to 1600 °C, and keep warm for 3 hours to obtain the first mixed gas.

[0083] 2) The first mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0084] 3) After the precursor material is crushed and sieved, it is then coated with titanium carbide. Specifically, 80g of metallic titanium powder and 210g of phenolic resin are mixed evenly and placed in a high-temperature vacuum furnace. The vacuum is evacuated to 30Pa, heated to 1600℃, and held for 2 hours to obtain a third mixed gas. Argon gas with a flow rate of 5L / min is introduced as the carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace. The gas is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved, and demagnetized to obtain potassium-ion battery anode material.

[0085] The potassium-ion battery anode material prepared in this embodiment was used to prepare a negative electrode sheet, and the battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0086] Example 4

[0087] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0088] 1) Weigh 1 kg of tin powder, 1.2 kg of tin dioxide powder, and 210 g of titanium hydroxide, mix them evenly, and place them in a high-temperature vacuum furnace. Evacuate the furnace to 130 Pa, heat it to 1900 °C, and introduce argon gas containing toluene at a flow rate of 5 L / min in a bubbling manner for 100 min. Keep it at this temperature for 1.5 hours to obtain the first mixed gas.

[0089] 2) The first mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled, and deposited on a stainless steel substrate to obtain the precursor material;

[0090] 3) After the precursor material is crushed and sieved, it is then coated with titanium carbide. Specifically, 130g of titanium hydroxide is placed in a high-temperature vacuum furnace, evacuated to 30Pa, heated to 1600℃, and propylene is introduced at a flow rate of 5L / min for 60min. The mixture is then kept at this temperature for 2 hours to obtain a third mixed gas. Argon gas at a flow rate of 5L / min is introduced as the carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace. The gas is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved, and demagnetized to obtain the potassium-ion battery anode material.

[0091] The potassium-ion battery anode material prepared in this embodiment was used to prepare a negative electrode sheet, and the battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0092] Example 5

[0093] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0094] 1) Weigh 1.3 kg of tin powder, 1.3 kg of tin dioxide powder, and 460 g of titanium dichloride, mix them evenly, place them in a high-temperature vacuum furnace, evacuate to 190 Pa, heat to 2000 °C, introduce natural gas at a flow rate of 15 L / min for 20 min, keep warm for 4 hours, and obtain the first mixed gas.

[0095] 2) The first mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0096] 3) After crushing and sieving the precursor material, titanium carbide coating treatment is performed. Specifically, 190g of titanium dichloride is placed in a high-temperature vacuum furnace, evacuated to 100Pa, heated to 1700℃, and natural gas is introduced at a flow rate of 3L / min for 85min. The mixture is then kept at this temperature for 3 hours to obtain a third mixed gas. Argon gas at a flow rate of 2L / min is introduced as the carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace. The gas is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved, and demagnetized to obtain a potassium-ion battery anode material with a titanium carbide coating layer.

[0097] The potassium-ion battery anode material prepared in this embodiment was used to prepare a negative electrode sheet, and the battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0098] Example 6

[0099] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0100] 1) Weigh 1.2 kg of tin powder and 1 kg of tin dioxide powder, mix them evenly, and place them in a high-temperature vacuum furnace. Evacuate the furnace to 5 Pa, heat it to 1200℃, and hold it for 2.5 hours to obtain a tin-containing mixed gas. Introduce methane gas at a flow rate of 10 L / min into the high-temperature vacuum furnace, and introduce the tetrabutyl titanate gas into the high-temperature vacuum furnace by bubbling through nitrogen gas at a flow rate of 3 L / min. Introduce the two gases for 1 hour, mix them evenly with the tin-containing mixed gas, and hold the furnace at 1200℃ for 2 hours to obtain a second mixed gas.

[0101] 2) The second mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0102] 3) After the precursor material is crushed and sieved, it is then coated with titanium carbide. Specifically, the high-temperature vacuum furnace is evacuated to 160 Pa, heated to 1800 °C, and methane gas at a flow rate of 3 L / min and nitrogen gas containing tetrabutyl titanate at a flow rate of 3 L / min are introduced by bubbling for 90 min. The mixture is then kept at this temperature for 2 hours to obtain a third mixed gas. Argon gas at a flow rate of 4.5 L / min is introduced as the carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace. The mixture is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved, and demagnetized to obtain the potassium-ion battery anode material.

[0103] The potassium-ion battery anode material prepared in this embodiment was used to prepare a negative electrode sheet, and the battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0104] Example 7

[0105] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0106] 1) Weigh 1.2 kg of tin powder and 1 kg of tin dioxide powder, mix them evenly, and place them in a high-temperature vacuum furnace. Evacuate the furnace to 30 Pa, heat it to 1500 °C, and hold it for 1.5 hours to obtain a tin-containing mixed gas. In a bubbling manner, introduce nitrogen gas at a flow rate of 8 L / min to carry toluene into the high-temperature vacuum furnace, and introduce ethyl acetoacetate titanium into the high-temperature vacuum furnace with nitrogen gas at a flow rate of 7 L / min. The two gases are introduced for 2 hours and mixed evenly with the above tin-containing mixed gas. The temperature in the high-temperature furnace is 1500 °C, and it is held for 5 hours to obtain a second mixed gas.

[0107] 2) The second mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0108] 3) After the precursor material is crushed and sieved, it is then coated with titanium carbide. Specifically, the high-temperature vacuum furnace is evacuated to 90 Pa and heated to 1600 °C. Nitrogen gas containing toluene and nitrogen gas containing ethyl acetoacetate titanium are introduced in a bubbling manner at a flow rate of 4 L / min and 3 L / min respectively for 100 min. The mixture is kept at this temperature for 2 hours to obtain a third mixed gas. Argon gas at a flow rate of 1 L / min is introduced as the carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace. The mixture is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved and demagnetized to obtain potassium-ion battery anode material.

[0109] The potassium-ion battery anode material prepared in this embodiment was used to prepare a negative electrode sheet, and the battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0110] Example 8

[0111] This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows:

[0112] 1) Weigh 1.2 kg of tin powder, 2 kg of tin dioxide powder and 290 g of titanium hydride, mix them evenly and place them in a high-temperature vacuum furnace, evacuate to 30 Pa, heat to 1750 °C, and introduce argon gas containing acetone at a flow rate of 5.5 L / min in a bubbling manner for 200 min, keep warm for 4 hours to obtain the first mixed gas.

[0113] 2) The first mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled and deposited on a stainless steel substrate to obtain the precursor material.

[0114] 3) After the precursor material is crushed and sieved, it is then coated with titanium carbide. Specifically, the high-temperature vacuum furnace is evacuated to 20 Pa, heated to 1500 °C, and methane gas at a flow rate of 1 L / min and nitrogen gas containing tetrabutyl titanate at a flow rate of 10 L / min are introduced by bubbling for 150 min. The mixture is then kept at this temperature for 2 hours to obtain a third mixed gas. Argon gas at a flow rate of 0.5 L / min is introduced as the carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace. The mixture is cooled and deposited on the surface of the precursor material. After discharge, the material is crushed, sieved, and demagnetized to obtain the potassium-ion battery anode material.

[0115] The potassium-ion battery anode material prepared in this embodiment was used to prepare a negative electrode sheet, and the battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0116] To better illustrate the effects of the embodiments of the present invention, a comparative example is provided to be made with the embodiments described above.

[0117] Comparative Example 1

[0118] This comparative example provides a preparation process and performance testing of a tin-based anode material without titanium carbide doping or a titanium carbide coating in the matrix. The specific preparation process is as follows:

[0119] 1) Mix 1 kg of tin powder and 1.2 kg of tin dioxide powder evenly, place them in a vacuum high-temperature furnace, evacuate to 140 Pa, heat to 1750 °C, and keep warm for 3 hours to obtain a mixed gas.

[0120] 2) The mixed gas is cooled and deposited on a stainless steel substrate to obtain the deposited material.

[0121] 3) After crushing and sieving the deposited material, tin-based anode material is obtained.

[0122] Carbon coating was performed on the tin-based anode material prepared in this comparative example: 1 kg of tin-based anode material was placed in a rotary furnace and heated to 950°C under a protective atmosphere. Argon gas, acetylene and natural gas were introduced in a volume ratio of 3:2:2 for gas phase coating. After holding at this temperature for 1.5 hours, the organic gas source was turned off. After cooling to room temperature, the material was discharged and graded to obtain the tin-based anode material with a carbon coating layer.

[0123] The tin-based anode material with a carbon coating prepared in this comparative example was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0124] The cycle curves of the full cells prepared from the tin-based anode material with carbon coating in this comparative example are shown below. Figure 2 As shown, the cycle performance of the full cell in Example 1 is better than that of the full cell in Comparative Example 1.

[0125] Comparative Example 2

[0126] This comparative example provides a preparation process and performance testing of a tin-based anode material with a titanium carbide coating but no titanium carbide doping in the matrix. The specific preparation process is as follows:

[0127] 1) Mix 1 kg of tin powder and 1.2 kg of tin dioxide powder evenly, place them in a vacuum high-temperature furnace, evacuate to 140 Pa, heat to 1750 °C, and keep warm for 3 hours to obtain a mixed gas.

[0128] 2) The mixed gas is cooled and deposited on a stainless steel substrate to obtain the deposited material.

[0129] 3) After crushing and sieving the deposited material, tin-based anode material is obtained.

[0130] 4) The tin-based anode material prepared in this comparative example was coated with titanium carbide. Specifically, the tin-based anode material was placed in the collection chamber of a high-temperature vacuum furnace. The high-temperature vacuum furnace was evacuated to 60 Pa and heated to 1700 °C. A mixture of acetylene and methane at a flow rate of 3 L / min and nitrogen containing tetrabutyl titanate at a flow rate of 8 L / min were introduced by bubbling for 120 min. The mixture was kept at this temperature for 2 hours to obtain a third mixed gas, wherein the volume ratio of acetylene to methane was 2:1. Argon gas at a flow rate of 0.5 L / min was introduced as the carrier gas to carry the third mixed gas into the collection chamber of the high-temperature vacuum furnace. The gas was cooled and deposited on the tin-based anode material. After crushing, sieving, and demagnetizing the deposited material, a tin-based anode material with a titanium carbide coating was obtained.

[0131] The tin-based anode material with a titanium carbide coating prepared in this comparative example was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0132] Comparative Example 3

[0133] This comparative example provides a preparation process and performance testing of a tin-based anode material with titanium carbide doping in the matrix but without a titanium carbide coating. The specific preparation process is as follows:

[0134] 1) Weigh 1.2 kg of tin powder, 1.2 kg of tin dioxide powder and 220 g of titanium hydride, mix them evenly and place them in a high-temperature vacuum furnace. Evacuate to 5 Pa, heat to 1850 °C, introduce ethylene at a flow rate of 5 L / min for 90 min, and keep warm for 4 hours to obtain the first mixed gas.

[0135] 2) The first mixed gas is cooled and deposited on a stainless steel substrate. The deposited material is then crushed and sieved to obtain a tin-based anode material doped with titanium carbide.

[0136] Carbon coating was performed on the titanium carbide-doped tin-based anode material prepared in this comparative example: 1 kg of titanium carbide-doped tin-based anode material was mixed with petroleum asphalt at a mass ratio of 28:1, placed in a high-temperature furnace, heated to 950℃ and held for 1.5 hours under a nitrogen atmosphere, cooled, discharged and graded to obtain titanium carbide-doped tin-based anode material with a carbon coating layer.

[0137] The titanium carbide-doped tin-based anode material with a carbon coating prepared in this comparative example was used to fabricate a negative electrode sheet and assemble a battery for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.

[0138] Table 1 summarizes the initial efficiency, reversible capacity, and cycle retention rate tests of the button cells in Examples 1-8 and Comparative Examples 1-3 after 100 and 300 full cell cycles.

[0139]

[0140] Table 1

[0141] As can be seen from the test data in Table 1, the cycle capacity retention of the full cells in Examples 1-8 after 250 cycles is superior to that of the full cells in Comparative Examples 1-3. This is because the substrates of Examples 1-8 are all doped with titanium carbide and have a titanium carbide coating layer, while the substrates of Comparative Examples 1-2 do not contain titanium carbide, and Comparative Example 3 does not have a titanium carbide coating layer. In Examples 1-8, titanium carbide is uniformly dispersed in the tin oxide substrate using chemical vapor deposition, and a titanium carbide layer is coated on the outer surface of the composite substrate of tin oxide and nano-titanium carbide. The high hardness of titanium carbide is utilized to achieve this effect. The internal titanium carbide, as an inert component that does not undergo potassium ion insertion / extraction, works together with the outer titanium carbide to stabilize the material's structure. This allows the material to buffer the volume expansion during the potassium ion insertion / extraction process of tin oxide during cycling, while also preventing the aggregation of tin oxide active materials. Furthermore, the high conductivity of titanium carbide enhances the conduction rate of potassium ions inside and outside the tin oxide layer, improving the overall conductivity of the negative electrode particles. Through the combined effect of the internal and external titanium carbide coatings, the potassium-ion battery exhibits characteristics such as low volume expansion, high rate capability, and long cycle life.

[0142] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A potassium-ion battery anode material, characterized in that, The potassium-ion battery anode material includes: a composite matrix of stannous oxide and nano-titanium carbide, and a titanium carbide coating layer covering the outer surface of the composite matrix. The composite matrix is ​​obtained by uniformly dispersing the nano-titanium carbide in the tin oxide matrix through chemical vapor deposition. The mass percentage of the nano-titanium carbide in the total mass of the composite matrix is ​​2%-20%; The mass of the titanium carbide coating layer accounts for 0.5%-10% of the total mass of the potassium-ion battery anode material.

2. The potassium-ion battery anode material according to claim 1, characterized in that, The average particle size Dv50 of the potassium-ion battery anode material is between 1 nm and 100 μm. The mass percentage of the nano-titanium carbide in the total mass of the composite matrix is ​​4%-15%. The mass of the titanium carbide coating layer accounts for 1.5%-6% of the total mass of the potassium-ion battery anode material.

3. A method for preparing the potassium-ion battery anode material according to any one of claims 1-2, characterized in that, The preparation method includes: A mixture of tin powder, tin dioxide, titanium source material, and hydrocarbons is placed in a high-temperature vacuum furnace and subjected to high-temperature heat treatment under a first reduced pressure condition to vaporize the mixture and obtain a first mixed gas; or a mixture of tin powder and tin dioxide is placed in a vacuum high-temperature furnace and subjected to high-temperature heat treatment under a second reduced pressure condition until the mixture vaporizes, and then the gas of titanium source material and hydrocarbons is introduced and thoroughly mixed to obtain a second mixed gas. The first or second mixed gas is introduced into the collection chamber of a high-temperature vacuum furnace, cooled, and deposited on a stainless steel substrate to obtain the precursor material. After the precursor material is crushed and sieved, it is then coated with titanium carbide to obtain the potassium-ion battery anode material.

4. The preparation method according to claim 3, characterized in that, The titanium source material includes one or more of the following: titanium tetrachloride, metallic titanium powder, titanium hydride, titanium hydroxide, titanium dioxide, titanium tetrachloride, titanium tetrabutyl ester, and ethyl acetoacetate titanium. The hydrocarbons include one or more of the following: methane, acetylene, ethylene, propylene, natural gas, propane, toluene, acetone, phenolic resin, and asphalt.

5. The preparation method according to claim 3, characterized in that, The high-temperature heat treatment under the first decompression condition specifically involves: evacuating to 1Pa-200Pa, heating to 1000℃-2000℃ and holding at that temperature for 0.5 hours-5 hours; The high-temperature heat treatment under the second decompression condition specifically involves: evacuating to 1Pa-200Pa, heating to 1000℃-2000℃ and holding at that temperature for 0.5 hours-5 hours.

6. The preparation method according to claim 3, characterized in that, The method for introducing the titanium source material gas and the hydrocarbon gas includes: directly introducing the titanium source material gas and the hydrocarbon gas into the high-temperature vacuum furnace, or introducing the titanium source material gas and the hydrocarbon gas into the high-temperature vacuum furnace by means of a carrier gas in a bubbling manner. The flow rate of the gas containing the titanium source material directly introduced into the high-temperature vacuum furnace is 2L / min-15L / min, and the introduction time is 20min-4 hours. The flow rate of the hydrocarbon gas directly introduced into the high-temperature vacuum furnace is 2L / min-15L / min, and the introduction time is 20min-4 hours. The carrier gas is argon or nitrogen, with a flow rate of 0.5 L / min to 8 L / min and an introduction time of 20 min to 4 hours.

7. The preparation method according to claim 3, characterized in that, The method for coating titanium carbide specifically involves placing a mixed powder of titanium source material and hydrocarbon in a high-temperature vacuum furnace and heat-treating it at high temperature under a third reduced pressure until the mixed powder vaporizes to obtain a third mixed gas. The third mixed gas is then carried into the collection chamber of the high-temperature vacuum furnace containing the precursor material by a carrier gas, allowing the third mixed gas to cool and deposit onto the surface of the precursor material. After discharge, the material is further crushed, sieved, and demagnetized to obtain a potassium-ion battery anode material. The titanium source material includes one or more of the following: titanium tetrachloride, metallic titanium powder, titanium hydride, titanium hydroxide, titanium dioxide, titanium tetrachloride, titanium tetrabutyl ester, and ethyl acetoacetate titanium. The hydrocarbons include one or more of the following: methane, acetylene, ethylene, propylene, natural gas, propane, toluene, acetone, phenolic resin, and asphalt; The high-temperature heat treatment under the third reduced pressure condition specifically involves: evacuating to 1Pa-200Pa, heating to 1000℃-2000℃ and holding at that temperature for 0.5 hours-5 hours; The carrier gas is argon or nitrogen, with a flow rate of 0.5 L / min to 8 L / min and an introduction time of 20 min to 4 hours.

8. A negative electrode sheet, characterized in that, The negative electrode sheet includes the potassium-ion battery negative electrode material as described in any one of claims 1-2.

9. A potassium-ion battery, characterized in that, The potassium-ion battery includes the negative electrode sheet as described in claim 8.

Citation Information

Patent Citations

  • MXene / rGO / stannic oxide nano composite material as well as preparation method and application thereof

    CN113697849A

  • Cathode active material, and a lithium secondary battery comprising the same

    KR1020160033003A